Rust-containing antirust coating and preparation method thereof

By using environmentally friendly raw materials such as biomass and biowax, combined with modified graphene and wax emulsion technology, a non-toxic and environmentally friendly rust-resistant coating with anti-rust paint was prepared, which solved the problems of pollution and insufficient adhesion of traditional paints, and achieved the dual effects of efficient rust and environmental protection.

CN119592138AInactive Publication Date: 2025-03-11XINYANG ZHONGHUI INSULATION MATERIALS CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411493259.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-24
Publication Date
2025-03-11
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Existing anti-rust coatings with rust have problems such as releasing VOC gas, polluting the environment and insufficient adhesion. Traditional solvent-based coatings contain toxic heavy metals, which affect the environment and human health.

Method used

Biomass and biowax are used as the main raw materials, combined with graphene and nanosilicon dioxide, and modified graphene and wax emulsion are prepared through ultrasonic oscillation and thermal reaction steps to form micelle aqueous dispersion and rust transfer agent and activator to form rust-resistant coatings.

Benefits of technology

It achieves a non-toxic, harmless, environmentally friendly rust-resistant effect, and also has excellent water resistance, salt spray resistance, adhesion ability and tensile strength, avoiding the harm of traditional paints to the environment and the human body.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005100624570000051
    Figure BDA0005100624570000051
Patent Text Reader

Abstract

The invention relates to the field of coatings, and discloses an on-rust antirust coating and a preparation method thereof. The environment-friendly biomass fuel comprises the following components in parts by weight: 100-120 parts of biomass, 10-15 parts of graphene, 80-100 parts of biological wax, 4-6 parts of nano silicon dioxide, 2-3 parts of a surfactant, 50-60 parts of a rust conversion agent, 25-30 parts of an activating agent, 20-30 parts of a silanization reagent, 4-5 parts of a cross-linking agent, 1-2 parts of an initiator, 1-2 parts of a dispersing agent, 2-4 parts of an emulsifying agent, 250-300 parts of ethanol, 200-300 parts of a 50% acetone aqueous solution and 30-45 parts of deionized water. According to the invention, the rust conversion agent is loaded on the graphene, and then the modified graphene is grafted on the biomass, so that the composite coating is endowed with rust resistance, and the water resistance, the salt fog resistance, the adhesive ability and the strength of the composite coating are improved; water is used as a dispersion medium and forms a water-based emulsion with the biological wax, and the prepared waterproof coating is a water-based coating and does not contain an organic solvent; in addition, the main raw materials biomass and biological wax are wide in source and have renewability, and secondary pollution is avoided after degradation.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of coatings, and in particular to a rust-proof coating and a preparation method thereof. Background Art

[0002] Rust-proof paint is a kind of rust-proof paint that can be directly applied on a certain rusty metal surface. It stabilizes, passivates or converts the rust, turning the active rust into harmless substances, so as to achieve the dual purpose of rust removal and protection. As people's living standards improve, people's requirements for the performance of paint are getting higher and higher. At present, most of the domestic rust-proof paints are solvent-based paints, which will release a large amount of VOC gas after spraying, which not only seriously endangers the health of users, but also pollutes the atmosphere and damages the ecological environment; in addition, in order to achieve the purpose of long-term rust prevention, most of them add rust-proof pigments containing toxic heavy metals such as zinc chrome yellow, which seriously pollutes the environment. At the same time, in acrylic anti-rust emulsions, acrylic monomers containing phosphate esters participate in acrylic emulsion polymerization, and use the combination of phosphoric acid functional groups and metal substrates to remove rust. The ability to turn rust is limited, and it cannot play a good role in rust prevention, and there are defects such as insufficient adhesion.

[0003] Biomass resources are of great significance in addressing climate change and solving environmental pollution problems. Biomass resources mainly come from organisms such as plants, animals and microorganisms. They are widely available, renewable, non-toxic and environmentally friendly. Biomass paint, also known as bio-based paint, is a new type of paint made from renewable biomass (such as plants, non-food crops and waste residues, etc.). With the improvement of environmental awareness and the continuous advancement of technology, biomass rust-proof paint is increasingly used in the market, including but not limited to construction, automobiles, furniture, home furnishing and other industries. For example, the biodegradable bio-resin paint developed by PPG and DSM has been applied to the field of interior wall paint; the automotive varnish developed by BASF, Covestro and Audi uses a bio-based curing agent; the native plant extract paint launched by Nippon Paint completely replaces petroleum resources with plant-based renewable resources; Akzo Nobel's Dulux brand has developed natural plant paints with high-efficiency formaldehyde removal, benzene resistance and antibacterial properties. Summary of the invention

[0004] In order to overcome the shortcomings and deficiencies of the prior art, the present invention aims to provide an anti-rust coating and a preparation method thereof. The prepared coating has anti-rust performance, excellent water resistance, salt spray resistance, adhesion ability and tensile strength, and is non-toxic, harmless and environmentally friendly.

[0005] The technical solution adopted by the present invention to solve its technical problem is:

[0006] A rust-proof paint comprises raw materials, measured by weight, comprising: 100-120 parts of biomass, 10-15 parts of graphene, 80-100 parts of biowax, 4-6 parts of nano silicon dioxide, 2-3 parts of surfactant, 50-60 parts of rust-removing agent, 25-30 parts of activator, 20-30 parts of silanization agent, 4-5 parts of cross-linking agent, 1-2 parts of initiator, 1-2 parts of dispersant, 2-4 parts of emulsifier, 250-300 parts of ethanol, 200-300 parts of 50% acetone aqueous solution and 30-50 parts of deionized water.

[0007] Preferably, the biomass is one of carboxymethyl cellulose, carboxymethyl chitosan, and dialdehyde starch, and the biowax is one of sugarcane wax, beeswax, and fruit wax.

[0008] Preferably, the surfactant is polydimethyldiallylammonium chloride.

[0009] Preferably, the rust-removing agent is tannic acid, and the activator is phosphatase A2.

[0010] Preferably, the silanization agent is one of vinyl silane, ethoxy silane and methacryloxy silane.

[0011] Preferably, the cross-linking agent is DCP, and the initiator is potassium persulfate.

[0012] Preferably, the dispersant is one of sodium pyrophosphate, sodium tripolyphosphate and sodium hexametaphosphate.

[0013] Preferably, the emulsifier is WSG-K02Y.

[0014] The preparation method of the rust-proof paint comprises the following steps:

[0015] (1) adding graphene and a rust-removing agent to 3 times the mass of deionized water and dispersing them by ultrasonic vibration for 20-30 minutes, then adding a surfactant, nano-silica, and a silanization agent, heating to 40-50° C. for reaction for 5-6 hours, then filtering, washing with deionized water for 2-3 times, and drying to obtain modified graphene;

[0016] (2) adding biomass, modified graphene, crosslinking agent, initiator and dispersant to ethanol, heating to 60-65° C. for reaction for 3 h, filtering after the reaction, washing with deionized water for 2-3 times, drying, and then dissolving in 50% acetone aqueous solution, placing in water for dialysis to obtain a micellar aqueous dispersion;

[0017] (3) adding bio-wax to the micellar water dispersion, heating to melt the bio-wax, mixing and stirring uniformly, and then adding an emulsifier and an activator, placing the mixture under ultrasound and stirring uniformly to form a wax emulsion, thereby obtaining a rust-proof coating.

[0018] Preferably, the heating temperature in step (3) is 5-8° C. higher than the melting point of the bio-wax used.

[0019] Beneficial effects of the present invention:

[0020] The present invention loads the rust-removing agent on graphene. The rust-removing agent tannic acid has strong reducing and chelating properties and can react with the metal surface and ions in the rust layer to form a dense protective film. This protective film can effectively block further corrosion of the metal by oxygen, water, chemicals, etc., thereby playing a role in rust prevention.

[0021] The present invention disperses the activator phosphatase A2 in a wax emulsion formed by bio-wax. Phosphatase A2 is a biological enzyme that can efficiently and specifically catalyze the hydrolysis of phosphate compounds. The phosphorus hydroxyl generated by the hydrolysis can form a phosphate metal salt with a metal matrix, form a passivation protective layer on the metal surface, connect the metal layer with the rust layer, and improve the rust-proofing effect of the coating as well as the adhesion, salt spray resistance and durability. However, as a protein, the biological enzyme is easily denatured and inactivated under the influence of environmental factors such as high temperature, acid, alkali, strong oxidizing groups, heavy metal salts, and some surfactants. Bio-wax is a high-quality hydrophobic material, and its waxy middle and high-level fatty acids and alcohols form a certain degree of crystalline area, with a dense structure. The wax emulsion formed by dispersing the biological wax in water has physical properties such as stability, no caking, and long shelf life, and also has chemical properties such as acid resistance, alkali resistance, and hard water resistance, which can well isolate water vapor, give the material excellent waterproof performance, and protect the biological enzyme from inactivation, and synergistically improve the rust-proofing effect of the rust-proofing agent with the biological enzyme.

[0022] The present invention modifies graphene and then closely combines it with biomass. Graphene is a two-dimensional layered nanomaterial with a large specific surface area. When coated on a metal surface, it can effectively further block water and oxygen migration, and synergistically improve the waterproofness, hardness, adhesion and strength of the composite coating.

[0023] The main raw materials of the present invention are biomass and biowax, which are widely available, renewable, environmentally friendly, and have no secondary pollution after degradation. The waterproof coating prepared by the present invention is a water-based coating, which uses water as a dispersion medium and does not contain organic solvents, so it does not contain harmful substances such as benzene, formaldehyde, free TDI and toxic heavy metals, is non-toxic and tasteless, harmless to the human body, and does not pollute the environment. DETAILED DESCRIPTION

[0024] The following is a further description of a rust-proof coating and a preparation method thereof of the present invention in combination with an embodiment. It is to be understood that the specific embodiments described herein are only used to explain the relevant invention, rather than to limit the invention.

[0025] Embodiment 1:

[0026] A rust-proof paint, the raw materials of which are measured by weight and composed of: 100 parts of carboxymethyl cellulose, 10 parts of graphene, 80 parts of sugarcane wax, 4 parts of nano silicon dioxide, 2 parts of polydimethyldiallylammonium chloride, 50 parts of tannic acid, 25 parts of phosphatase A2, 20 parts of vinyl silane, 4 parts of DCP, 1 part of potassium persulfate, 1 part of sodium pyrophosphate, 2 parts of WSG-K02Y, 250 parts of ethanol, 200 parts of 50% acetone aqueous solution, and 30 parts of deionized water.

[0027] The method for preparing the rust-proof coating described in this embodiment comprises the following steps, measured by weight:

[0028] (1) adding graphene and tannic acid to 3 times the mass of deionized water and dispersing them by ultrasonic vibration for 20-30 minutes, then adding polydimethyldiallylammonium chloride, nano-silica, and vinyl silane, heating to 40-50° C. for reaction for 5-6 hours, then filtering, washing with deionized water twice, and drying to obtain modified graphene;

[0029] (2) adding carboxymethyl cellulose, modified graphene, DCP, potassium persulfate, and sodium pyrophosphate to ethanol, heating to 60-65° C. for reaction for 3 h, filtering after the reaction, washing with deionized water twice, drying, and then dissolving in a 50% acetone aqueous solution, and dialyzing in water to obtain a micellar aqueous dispersion;

[0030] (3) Add sugarcane wax to the micellar aqueous dispersion, heat to 90° C. to melt the sugarcane wax, stir the mixture evenly, then add WSG-K02Y and phosphatase A2, stir the mixture evenly under ultrasound to form a wax emulsion, and obtain a rust-resistant coating.

[0031] Embodiment 2:

[0032] The invention discloses an anti-rust paint. The raw materials thereof are measured by weight and are composed of: 110 parts of carboxymethyl chitosan, 12 parts of graphene, 90 parts of beeswax, 5 parts of nano-silicon dioxide, 2 parts of polydimethyldiallylammonium chloride, 55 parts of tannic acid, 27 parts of phosphatase A2, 25 parts of ethoxysilane, 5 parts of DCP, 2 parts of potassium persulfate, 2 parts of sodium tripolyphosphate, 3 parts of WSG-K02Y, 275 parts of ethanol, 250 parts of 50% acetone aqueous solution and 40 parts of deionized water.

[0033] The method for preparing the rust-proof coating described in this embodiment comprises the following steps, measured by weight:

[0034] (1) adding graphene and tannic acid to 3 times the mass of deionized water and dispersing them by ultrasonic vibration for 20-30 minutes, then adding polydimethyldiallylammonium chloride, nano-silicon dioxide, and ethoxysilane, heating to 40-50° C. for reaction for 5-6 hours, then filtering, washing with deionized water 3 times, and drying to obtain modified graphene;

[0035] (2) adding carboxymethyl chitosan, modified graphene, DCP, potassium persulfate, and sodium tripolyphosphate to ethanol, heating to 60-65° C. for reaction for 3 h, filtering after the reaction, washing with deionized water for 3 times, drying, and then dissolving in 50% acetone aqueous solution, placing in water for dialysis to obtain a micellar aqueous dispersion;

[0036] (3) Add beeswax to the micellar aqueous dispersion, heat to 75° C. to melt the beeswax, stir the mixture evenly, then add WSG-K02Y and phosphatase A2, stir the mixture evenly under ultrasound to form a wax emulsion, and obtain a rust-resistant coating.

[0037] Embodiment 3:

[0038] A rust-proof paint comprises raw materials, measured by weight, comprising: 100-120 parts of dialdehyde starch, 10-15 parts of graphene, 80-100 parts of fruit wax, 4-6 parts of nano silicon dioxide, 2-3 parts of polydimethyldiallylammonium chloride, 60 parts of tannic acid, 30 parts of phosphatase A2, 20-30 parts of methacryloxysilane, 4-5 parts of DCP, 1-2 parts of potassium persulfate, 1-2 parts of sodium hexametaphosphate, 2-4 parts of WSG-K02Y, 250-300 parts of ethanol, 200-300 parts of 50% acetone aqueous solution and 30-50 parts of deionized water.

[0039] The method for preparing the rust-proof coating described in this embodiment comprises the following steps, measured by weight:

[0040] (1) adding graphene and tannic acid to 3 times the mass of deionized water and dispersing them by ultrasonic vibration for 20-30 minutes, then adding polydimethyldiallylammonium chloride, nano-silicon dioxide, and methacryloxysilane, heating to 40-50° C. for reaction for 5-6 hours, then filtering, washing with deionized water 3 times, and drying to obtain modified graphene;

[0041] (2) adding dialdehyde starch, modified graphene, DCP, potassium persulfate, and sodium hexametaphosphate to ethanol, heating to 60-65° C. for reaction for 3 h, filtering after the reaction, washing with deionized water for 3 times, drying, and then dissolving in a 50% acetone aqueous solution, and dialyzing in water to obtain a micellar aqueous dispersion;

[0042] (3) Add fruit wax to the micellar water dispersion, heat to 65°C to melt the fruit wax, stir and mix evenly, then add WSG-K02Y and phosphatase A2, stir and mix evenly under ultrasound to form a wax emulsion, and obtain a rust-proof coating.

[0043] Comparative Example 1:

[0044] The difference between this comparative example and Example 1 is that no biowax is added to all the raw materials, and the other raw materials and steps are the same as those in Example 1.

[0045] Comparative Example 2:

[0046] The difference between this comparative example and Example 1 is that graphene is not added to all the raw materials, and the other raw materials and steps are the same as those in Example 1.

[0047] Comparative Example 3:

[0048] The difference between this comparative example and Example 1 is that no rust remover and activator are added to all the raw materials, and the other raw materials and steps are the same as those in Example 1.

[0049] Waterproof coating performance test:

[0050] The waterproof coatings prepared in Examples 1-3 and Comparative Examples 1-2 were coated on a steel plate with a thickness of 125 μm. After being surface dried at room temperature, their performance was tested. Some reference standards include: GB / T 16777-2008 (tensile strength); GB / T 6739-1996 (hardness); GB / T 1733-1993 (water resistance); GB / T 10125 (salt spray resistance); GB / T 1720-1979 (adhesion); GB / T18883-2002 (VOC, i.e., volatile organic compounds).

[0051] Table 1: Waterproof coating performance test results

[0052]

[0053] As can be seen from the above table, the water resistance, salt spray resistance and adhesion of Comparative Example 1 are worse than those of Example 1. This is because no biowax is added in Comparative Example 1, while Example 1 contains biowax. Biowax is a high-quality hydrophobic material. The higher fatty acids and alcohols in its wax form a certain degree of crystalline area, which has a dense structure and can well isolate water vapor, giving the material excellent waterproof performance. In addition, due to the protection of biowax, the activator phosphatase A2 is not easy to inactivate, and the rust-proof effect is good. The dense passivation protective layer formed improves the water resistance, salt spray resistance and adhesion of the coating. The tensile strength, hardness and water resistance of Comparative Example 2 are worse than those of Example 1. This is because no graphene is added in Comparative Example 2, while modified graphene is contained in Example 1. The two-dimensional layered structure of graphene is closely combined with biomass, which improves the waterproofness, hardness, adhesion and strength of the composite coating. The strength, hardness, water resistance, salt spray resistance and adhesion of Comparative Example 3 are all inferior to those of Example 1. This is because no rust-removing agent and activator are added in Comparative Example 3, while Example 1 contains rust-removing agent and activator. The rust-removing agent tannic acid has strong reducing and chelating properties, and can react with the metal surface and ions in the rust layer to form a dense protective film, effectively blocking further corrosion of the metal by oxygen, water, chemicals, etc., thereby playing a role in rust prevention. In addition, tannic acid can also synergize with other additives such as surfactants, organic high molecular polymers, etc., to promote the close combination between the subsequent anti-rust paint film and the metal substrate, greatly improving the overall adhesion, salt spray resistance and durability of the anti-rust coating.

[0054] The VOC contents of Examples 1-3 and Comparative Examples 1-3 are very small. This is because the present invention uses water as a dispersion medium and does not contain organic solvents. Therefore, it does not contain harmful substances such as benzene, formaldehyde, free TDI and toxic heavy metals, and is environmentally friendly.

[0055] The above embodiments are only part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments of the present invention, other embodiments obtained by those skilled in the art without creative work shall all fall within the scope of protection of the present invention.

Claims

1. A rust-proof paint, characterized in that: The raw materials include, by weight, 100-120 parts of biomass, 10-15 parts of graphene, 80-100 parts of biowax, 4-6 parts of nano silicon dioxide, 2-3 parts of surfactant, 50-60 parts of rust remover, 25-30 parts of activator, 20-30 parts of silanization agent, 4-5 parts of cross-linking agent, 1-2 parts of initiator, 1-2 parts of dispersant, 2-4 parts of emulsifier, 250-300 parts of ethanol, 200-300 parts of 50% acetone aqueous solution and 30-45 parts of deionized water.

2. The rust-proof paint according to claim 1, characterized in that: The biomass is one of carboxymethyl cellulose, carboxymethyl chitosan and dialdehyde starch, and the biowax is one of sugarcane wax, beeswax and fruit wax.

3. The rust-proof paint according to claim 1, characterized in that: The surfactant is polydimethyldiallylammonium chloride.

4. The rust-proof paint according to claim 1, characterized in that: The rust-removing agent is tannic acid, and the activator is phosphatase A2.

5. The rust-proof paint according to claim 1, characterized in that: The silanization agent is one of vinyl silane, ethoxy silane and methacryloxy silane.

6. The rust-proof paint according to claim 1, characterized in that: The cross-linking agent is DCP, and the initiator is potassium persulfate.

7. The rust-proof paint according to claim 1, characterized in that: The dispersant is one of sodium pyrophosphate, sodium tripolyphosphate and sodium hexametaphosphate.

8. The rust-proof paint according to claim 1, characterized in that: The emulsifier is WSG-K02Y.

9. The method for preparing a rust-proof coating according to any one of claims 1 to 8, characterized in that: The preparation method comprises the following steps: (1) adding graphene and a rust-removing agent to 3 times the mass of deionized water and dispersing them by ultrasonic vibration for 20-30 minutes, then adding a surfactant, nano-silica, and a silanization agent, heating to 40-50° C. for reaction for 5-6 hours, then filtering, washing with deionized water for 2-3 times, and drying to obtain modified graphene; (2) adding biomass, modified graphene, crosslinking agent, initiator and dispersant to ethanol, heating to 60-65° C. for reaction for 3 h, filtering after the reaction, washing with deionized water for 2-3 times, drying, and then dissolving in 50% acetone aqueous solution, placing in water for dialysis to obtain a micellar aqueous dispersion; (3) adding bio-wax to the micellar water dispersion, heating to melt the bio-wax, mixing and stirring uniformly, and then adding an emulsifier and an activator, placing the mixture under ultrasound and stirring uniformly to form a wax emulsion, thereby obtaining a rust-proof coating.

10. The method for preparing a rust-proof and anti-rust coating according to claim 9, characterized in that: The heating temperature in step (3) is 5-8° C. higher than the melting point of the biowax used.

Citation Information

Patent Citations

  • Flame-retardant waterproof coating for interior wall of building and preparation method thereof

    CN104650714A

  • Waterborne antirust coating with rust and preparation method thereof

    CN108117819A

  • Water-based paint and preparing method thereof

    CN108285697A

  • Room-temperature self-crosslinking coating and preparation method thereof

    CN114316721A